2005
DOI: 10.1152/physiol.00015.2005
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Protein Interactions in the Tetraspanin Web

Abstract: Tetraspanins are evolutionarily conserved membrane proteins that tend to associate laterally with one another and to cluster dynamically with numerous partner proteins in membrane microdomains. Consequently, members of this family are involved in the coordination of intracellular and intercellular processes, including signal transduction; cell proliferation, adhesion, and migration; cell fusion; and host-parasite interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
230
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(237 citation statements)
references
References 70 publications
(65 reference statements)
3
230
0
4
Order By: Relevance
“…Therefore, CD81 shed from the placenta into the maternal circulation may mediate the dysfunction of maternal endothelial cells and drive the development of the maternal manifestations of sPE. To test this hypothesis, it may be important to understand the molecular mechanisms of placental original CD81 webs or tetraspaninenriched microdomains (36).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CD81 shed from the placenta into the maternal circulation may mediate the dysfunction of maternal endothelial cells and drive the development of the maternal manifestations of sPE. To test this hypothesis, it may be important to understand the molecular mechanisms of placental original CD81 webs or tetraspaninenriched microdomains (36).…”
Section: Discussionmentioning
confidence: 99%
“…This is mainly due to the existence of the largest, conserved domain, known as the large extracellular loop (LEL). Members of the tetraspanin family from different organisms are structurally and functionally related [18,31]. Phylogenetic analysis indicated that TSP2 of E. multilocularis is phylogenetically related to TSP2 [15], Sm23 [20] and SJC23 [21,22] of Schistosoma, the protective antigens against schistosomiasis, while TSP5 is closely related to the T24 antigen of T. solium, a diagnostic antigen for cysticercosis [26].…”
Section: Discussionmentioning
confidence: 99%
“…cell fusion, and host-parasite interactions [18]. The host-parasite interactions are thought to be associated with immune evasion [19], which has resulted in the use of tetraspanins as vaccines interfering with the schistosome survival strategy [19][20][21][22].…”
mentioning
confidence: 99%
“…Tetraspanins are expressed in all human cell types, and most cells generally express multiple tetraspanins (Levy 2005). Tetraspanins may be expressed on both the cell surface and on granular membranes (Israels 2005).…”
Section: Tetraspanin Structurementioning
confidence: 99%
“…Generally, the extracellular domains-mainly EC2-interact with laterally associated proteins or soluble ligands, the cytosolic regions associate with cytoskeletal or signaling molecules, and the transmembrane domains interact with other proteins necessary for maintenance of the tetraspanin web (Levy 2005). Thus, the tetraspanin web acts as a molecular facilitator, organizing membrane proteins and coupling receptors to signaling pathways (Levy 2005). …”
Section: Tetraspanin Webmentioning
confidence: 99%